Politics once removed: Everyday international relations in the 2014 military Operation RECSYR - Christine Nissen; Jessica Larsen (Danish Institute for International Studies (DIIS), 2021)
International relations play out on multiple frequencies, where adversary states in one conflict may be partners in another. How do such shifting circumstances influence the conditions for ongoing international military operations? This paper seeks answers through an analysis of Operation RECSYR, the 2014 Danish-led naval intervention to remove chemical weapons from Syria. It was carried out by the UN and key states - including Denmark, Norway, and Russia. Yet this was also a period of highly tense relations between the West and Russia due to the latter's involvement with President Assad in the Syrian war, and the annexation of Crimea. Thus, the successful cooperation largely hinged on the tactical level, and the politics of the day needed to be set to one side. Drawing on Bourdieu's theoretical 'practice approach' to 'field analysis', this article opens up 'the black box' of the state to look at everyday international relations. It uncovers how military practitioners facilitated cooperation despite a conflict-ridden political context. The paper argues that the conditions for international operations neither leave military practitioners in a stalemate, nor are they impervious to strategic-level politicking. Rather, it is the capacity of the tactical level to shift between using and then decoupling its culture and practices from shifts and conflicts playing out on the strategic level that produces the everyday international relations.
Keywords: 330; Defence and security policy; Danish and European foreign policies; World politics; The politics of great and emerging powers; Fragile states